Shocking Choice: Trade Shocks, Local Labor Markets and Vocational Occupation Choices - Lisa Simon (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Whether individuals choose occupations that teach general or specific skills can have important implications on how protected they are from changing conditions on the labor market. This paper looks at the impact of growing up in a region exposed to structural change caused by import competition on vocational occupation choices using longitudinal social security data for Germany. Results show that individuals enter more skill-specific occupations like manufacturing and less general occupations like services if exposed to higher local import competition. Lifetime earnings are adversely affected, which can be attributed to vocational occupation choices.
Keywords: J24; J21; F14; 330; Trade shocks; occupational choice; vocational education; occupational skill specificity; local labor markets